Protection of Migrant Workers in Suriname: How do Indonesian Representatives Implement International Labour Organization Conventions? - Maharani Wibisono, Lutecia Zahra; Sadiawati, Diani (Udayana Journal of Law and Culture; Vol 5 No 2 (2021), 2021)
In June 2020, sixteen Indonesian migrant workers (IMW) who worked as fishing boat crew in a Surinamese company fled to the Indonesian Embassy in Paramaribo, Suriname to acquire protection and assistance. They revealed that the company had failed to uphold their rights, committed inhuman treatment, and resulted in numerous losses. The embassy then immediately exercised a consular function to protect their safety and tried to facilitate the demands of those sailors to relevant parties and local authorities. The article aims to analyze the role of Indonesian representatives to protect the rights of Indonesian migrant workers in Suriname based on the International Labour (ILO) conventions. It is juridical empirical research that was conducted through visiting and field research to the Indonesian Embassy in Suriname in November 2020. The research suggested that Indonesian representatives in Suriname have played a significant role in advocating the IMW rights through all possible means, including mediation, negotiation, and diplomatic channels. In addition, there is a need to create a Memorandum of Understanding between Indonesia and Suriname to ensuring proper protection for migrant workers.